2009
DOI: 10.1080/14767050802609759
|View full text |Cite
|
Sign up to set email alerts
|

Cord blood biomarkers of the fetal inflammatory response

Abstract: In current neonatal practice, clinical signs of intrauterine infection (IUI) are often non-specific. From a large panel of immune biomarkers, we seek to identify cord blood markers that are most strongly associated with the fetal inflammatory response (FIR), a specific placental lesion associated with serious neonatal complications. We used multiplex immunoassay to measure 27 biomarkers, selected as part of an NIH-funded study of preterm birth, according to gestational age(GA) and extent of placental inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 28 publications
1
39
0
Order By: Relevance
“…Umbilical cord plasma IL-8, IL-10, and MCP-1 concentrations were significantly associated with FIRS. Our findings are consistent with those of Mestan et al, who used multiplex immunoassays and reported that, among the 27 cord blood biomarkers examined, the concentrations of IL-1β, IL-6, and IL-8 were associated with the presence of funisitis (the magnitude of association was stronger for IL-6 and IL-8 than for IL-1β) [268]. …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Umbilical cord plasma IL-8, IL-10, and MCP-1 concentrations were significantly associated with FIRS. Our findings are consistent with those of Mestan et al, who used multiplex immunoassays and reported that, among the 27 cord blood biomarkers examined, the concentrations of IL-1β, IL-6, and IL-8 were associated with the presence of funisitis (the magnitude of association was stronger for IL-6 and IL-8 than for IL-1β) [268]. …”
Section: Discussionsupporting
confidence: 92%
“…Several studies have demonstrated the potential value of umbilical cord plasma concentrations of IL-6 [105, 250277] and IL-8 [257, 260262, 267, 268, 276, 278, 279] for the identification of intra-amniotic infection and early-onset neonatal sepsis. Our findings are consistent with those of Lencki et al, who reported that neonates born to mothers with clinical chorioamnionitis had higher umbilical cord plasma concentrations of IL-6, but not IL-1β and soluble IL-2 receptor, than those without this condition [280].…”
Section: Discussionmentioning
confidence: 99%
“…Placental inflammation is associated with early onset neonatal infection [2325], although only a fraction of infants with histologic chorioamnionitis develop EOS [22]. Some cord blood biomarker levels are associated with placental inflammation representing a neonatal response to a perinatal insult [26, 27]. Although the role of placental histopathology in the diagnosis of neonatal sepsis and treatment decisions remains unclear [28], placental inflammation may be a useful tool to identify infants exposed to intraamniotic infection.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the protein concentration differences between the preterm and the full term might reflect environmental, obstetrical and neonatal influences, just as readily as developmental regulation [15]. …”
Section: Introductionmentioning
confidence: 99%